Concussed or Not? An Assessment of Concussion Experience and Knowledge Within Elite and Semiprofessional Rugby Union. Issue 4 (July 2016) - Mathema, Prabhat; Evans, Daniel; Moore, Isabel S.; Ranson, Craig; Martin, Rhodri
Abstract : Objective: The primary aim was to assess experience and knowledge of adult concussion among international, professional and semiprofessional players, coaches, medical staff, and referees within Rugby Union. The secondary aim was to identify preferred education dissemination routes. Design: Questionnaires devised specifically for players, coaches, medical staff, and referees. Setting and Participants: A total of 370 players, 44 coaches, 40 medical staff, and 33 referees from within Wales were surveyed. Main Outcome Measures: Knowledge of the signs and symptoms of concussion, return to play guidelines and consequences of concussion were investigated along with experiences of, and attitudes towards, concussion. Results: The respondents had extensive experience of sustaining or witnessing rugby-related concussion. Medical staff had the greatest level of concussion knowledge, with coaches having the least. Players and coaches exhibited a disconnection between being "knocked-out" and practically applying this when managing concussion. Almost half of the players and coaches did not indicate concussion could impair performance. Eighty percent of medical staff had felt pressured to clear a concussed player. Most players (82%), coaches (66%), and referees (64%) incorrectly believed protective equipment prevents concussion. Players and coaches prefer concussion education from medical staff, whereas medical staff and referees prefer such education from governing body Web sites or training courses. Conclusions: Several role-specific misconceptions and deficiencies in concussion knowledge were identified and should be targeted through education. Medical staff had the highest level of concussion knowledge and were the preferred sources of education for players and coaches. Therefore, they are encouraged to play a greater role in providing concussion education. Abstract : Supplemental Digital Content is Available in the Text.